Comparison of maintenance with decitabine or chemotherapy in a real-world cohort of patients with acute myeloid leukemia - Wei, Zhi-Feng; Yan, Jia-Qi; Tan, Ye-Hui; Lin, Hai; Liu, Qiu-Ju; Liu, Xiao-Liang; Su, Long; Gao, Su-Jun (Frontiers in Pharmacology, 2026)
BackgroundThe objective of this real-world cohort study was to evaluate the efficacy and safety of decitabine versus conventional chemotherapy in the maintenance therapy (MT) of patients with acute myeloid leukemia (AML).MethodsData were collected from 156 consecutive patients diagnosed with AML at our center. All patients achieved complete remission (CR) after 1–2 courses of induction therapy, followed by consolidation with high-dose cytarabine (HiDAC). MT was administered using either decitabine or conventional chemotherapy, while patients who did not receive maintenance served as controls.ResultsMT significantly improved both relapse-free survival (RFS) and overall survival (OS) in AML patients. However, no significant difference was observed between decitabine and conventional chemotherapy. MT notably prolonged both RFS and OS in the cytogenetic intermediate-risk group, patients without FLT3-ITD mutations, and those achieving CR after one course of induction therapy. The benefits of MT were not influenced by the European Leukemia Net (ELN) risk category, measurable residual disease (MRD) status, or the number of HiDAC courses. Compared with chemotherapy, decitabine maintenance significantly improved RFS and OS in patients who received 3–4 courses of treatment. Additionally, the incidence of adverse reactions was significantly lower in the decitabine group than in the chemotherapy arm.ConclusionMT with either decitabine or chemotherapy can improve outcomes of AML patients in this real-world cohort. Decitabine maintenance exhibits better tolerability compared with chemotherapy and enhances survival in specific patient subgroups.